2021
DOI: 10.1186/s12711-021-00682-7
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive genome-wide scan detects genomic regions related to local adaptation and climate resilience in Mediterranean domestic sheep

Abstract: Background The management of farm animal genetic resources and the adaptation of animals to climate change will probably have major effects on the long-term sustainability of the livestock sector. Genomic data harbour useful relevant information that needs to be harnessed for effectively managing genetic resources. In this paper, we report the genome characterization of the highly productive Mediterranean Chios dairy sheep and focus on genetic diversity measures related with local adaptation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 97 publications
(96 reference statements)
3
18
2
1
Order By: Relevance
“…Considering the estimated statistics using a window or sliding window can cause some analytical bias; hence, the consecutive run test was applied, which has been suggested to be more accurate ( Santos et al, 2021 ) to detect genome-wide ROH and ROHet. Due to diverse computational parameters, tested populations, SNP arrays, and the number and length of ROH and ROHet obtained herein were different than those obtained from previous studies in cattle ( Biscarini et al, 2020 ), turkeys ( Marras et al, 2018 ), horses ( Santos et al, 2021 ), and sheep ( Tsartsianidou et al, 2021 ). For example, the average number of ROHet detected per animal (45.50 in this study) was higher than that detected by other studies in cattle (9.87) ( Biscarini et al, 2020 ) and sheep (28.28) ( Tsartsianidou et al, 2021 ) and lower than that detected in turkeys (57.80) ( Marras et al, 2018 ) and horses (52.17) ( Santos et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…Considering the estimated statistics using a window or sliding window can cause some analytical bias; hence, the consecutive run test was applied, which has been suggested to be more accurate ( Santos et al, 2021 ) to detect genome-wide ROH and ROHet. Due to diverse computational parameters, tested populations, SNP arrays, and the number and length of ROH and ROHet obtained herein were different than those obtained from previous studies in cattle ( Biscarini et al, 2020 ), turkeys ( Marras et al, 2018 ), horses ( Santos et al, 2021 ), and sheep ( Tsartsianidou et al, 2021 ). For example, the average number of ROHet detected per animal (45.50 in this study) was higher than that detected by other studies in cattle (9.87) ( Biscarini et al, 2020 ) and sheep (28.28) ( Tsartsianidou et al, 2021 ) and lower than that detected in turkeys (57.80) ( Marras et al, 2018 ) and horses (52.17) ( Santos et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 76%
“…Due to diverse computational parameters, tested populations, SNP arrays, and the number and length of ROH and ROHet obtained herein were different than those obtained from previous studies in cattle ( Biscarini et al, 2020 ), turkeys ( Marras et al, 2018 ), horses ( Santos et al, 2021 ), and sheep ( Tsartsianidou et al, 2021 ). For example, the average number of ROHet detected per animal (45.50 in this study) was higher than that detected by other studies in cattle (9.87) ( Biscarini et al, 2020 ) and sheep (28.28) ( Tsartsianidou et al, 2021 ) and lower than that detected in turkeys (57.80) ( Marras et al, 2018 ) and horses (52.17) ( Santos et al, 2021 ). Nevertheless, our results were consistent with these studies wherein the short segment of ROH (<2 Mb) and ROHet (<1 Mb) showed the largest proportion, and ROHet were much rarer and shorter than ROH.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Estas tecnologías han permitido la identificación de marcadores moleculares en genes candidatos asociados a indicadores de termo-tolerancia (Luna-Nevárez et al, 2020, fertilidad (Luna-Nevárez et al, 2011;Angulo-Valenzuela et al, 2021), crecimiento (Weng et al, 2016) y caracteres de calidad de la canal (Peters et al, 2013). Regiones genómicas han sido reportadas como asociadas a procesos de adaptación y resistencia a los efectos del cambio climático en ovinos (Tsartsianidou et al, 2021). Además, la tecnología de secuenciación de ARN (RNA-Seq) ha facilitado el descubrimiento de nuevos transcritos (transcriptómica), la identificación de sus genes correspondientes, así como la medición de su expresión a través de métodos como la reacción en cadena de la polimerasa cuantitativa (qPCR; Kukurba y Montgomery, 2015).…”
unclassified